The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1155/2020/5096201
|View full text |Cite
|
Sign up to set email alerts
|

Time to Recovery and Its Predictors among Children 6–59 Months Admitted with Severe Acute Malnutrition to East Amhara Hospitals, Northeast Ethiopia: A Multicenter Prospective Cohort Study

Abstract: Background. Malnutrition has been among the most common public health problems in the world, especially in developing countries including Ethiopia. Even though the Ethiopian government launched stabilization centers in different hospitals, there are limited data on how long children will stay in treatment centers to recover from severe acute malnutrition. This study aimed to assess the time to recovery and its predictors among children 6–59 months with severe acute malnutrition admitted to public hospitals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
2
5
1
Order By: Relevance
“…This reduced incidence of recovery with increased duration of hospital stay might be attributable to inpatient complications and increased risk of nosocomial infections. It is comparable with the study findings from Addis Ababa (4.6) [24], Southern Ethiopia (3.61) [15], Jimma (4.06) [18], East Amhara Hospitals(6.9) [10], Pawi, Benishangul Gumuz(5.3) [22]. This might be due to the relative similarity in readiness of health care facilities and socio economic characteristics of the study subjects.…”
Section: Plos Onesupporting
confidence: 87%
See 3 more Smart Citations
“…This reduced incidence of recovery with increased duration of hospital stay might be attributable to inpatient complications and increased risk of nosocomial infections. It is comparable with the study findings from Addis Ababa (4.6) [24], Southern Ethiopia (3.61) [15], Jimma (4.06) [18], East Amhara Hospitals(6.9) [10], Pawi, Benishangul Gumuz(5.3) [22]. This might be due to the relative similarity in readiness of health care facilities and socio economic characteristics of the study subjects.…”
Section: Plos Onesupporting
confidence: 87%
“…However, the median time of recovery in this study is far faster than the median recovery time reported in Dire Dawa (61 days) [12], Arba Minch(49 days) [16], and Southern Ethiopia(26 days) [15] and a bit faster than recovery time reported in Jimma(19 days) [18]. However, it is a bit longer duration compared to recovery time reported in the Amhara region [10,11]. The present study found an overall incidence rate of 5.28 per 100 child day's observation with the highest incidence of recovery during 15-20 days((20.06 per 100 child days' followup) followed by 20-25 days(13.63 per 100 child days' observations).…”
Section: Plos Onecontrasting
confidence: 76%
See 2 more Smart Citations
“…The sample size was calculated for both objectives (prevalence of achieving adequate weight gain and factors associated with it); the larger sample size was found by using a single population proportion formula for calculation of prevalence, taking the proportion of treated children with SAM who achieved adequate average weight gain as 71.3%, 17 a significance level of 0.05, a 95% confidence interval (CI), a margin of error of 5% and a 10% incompleteness rate. The final calculated sample size was 332.…”
Section: Methodsmentioning
confidence: 99%